Theoretical views of the fault nature (Journal of actual problems of jurisprudence, 2018)
In this article the author gives the analysis to theoretical questions of concept of fault in civil law. Fault, being legal concept, also has historical roots, in different historical formations scientists considered fault and responsibility from various positions. In the majority of civil literature the following definition of fault meets: «The fault is a mental attitude of the person towards the behavior in the form of intention or imprudence, and to the come consequences». According to some scientists it is necessary to exclude completely mental aspects in definition of fault. Other authors consider that the fault without fail has to be considered when attracting to civil responsibility.Key words: the obligation, the delict, fault (culpa), intention (dolus), imprudence (negligentia) on the Roman private law.